(MIS)USAGE OF RHETORIC – EXAMPLES FROM ANCIENT TIMES TO THE MODERN STATE OF NATIONAL SURVEILLANCE - Avramović, Dragutin; Jovanov, Ilija D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The art of beautiful speech has its origins in the ancient Greek tradition. In sophistic discussions of justice and truth, eloquence played a notable role. Plato did not deny the importance of the art of persuasion, but he pointed out the difference between the knowledge provided by philosophy and the belief that is a consequence of persuasion. Therefore, the authors try to shed light on whether rhetoric is a morally neutral skill with a great ability to relativize. In this sense, Kelsen's critique of the natural law concepts of justice and truth are considered. Due to the impossibility of their absolute determination, Kelsen emphasized the fateful significance of theological teachings and rhetoric that convinced people of the existence of the one and only value system that is the basis of all norms. Thus, it turned out that rhetoric was extremely important for natural law, but its significance is even greater today. The changes brought by the modern age, among which a special place is occupied by endangering the privacy of citizens due to the collecting personal data and strengthening the culture of surveillance, especially emphasize the need to use the finest tuned rhetorical elements. Convincing the existence of absolute norms turned into convincing the need for perpetual surveillance of citizens in order to ensure their survival. Therefore, the authors conclude that rhetoric is a morally neutral skill with great potential for everyday (mis)use and that in the current circumstances it has an advantage over philosophical considerations about absolute values. At the same time, the authors point out that such an abuse of the art of persuasion will lead to the other extremity from which people will seek a way out by returning to philosophy.